O dever de revelação como problema de independência e imparcialidade dos árbitros - Almeida, Daniela Vicente de (2021)
This dissertation focuses on the arbitrator’s duty of disclosure. In contrast to national doctrine, this is one of the most current subjects in arbitration since it is frequently discussed in jurisprudence. Nonetheless, it is rather superficially regulated in several arbitration rules, such as LAV. Briefly, the duty of disclosure consists on the arbitrator’s obligation to reveal any facts that might raise justifiable doubts as to his or her impartiality or independence, as fundamental principles of arbitrator’s conduct. Taking this into account, this dissertation was written based on some fundamental approachs: firstly, the studying of arbitration’s hybrid nature, from which it is possible to recognize the private justice pursued by arbitrators. Secondly, the thorough analysis of ethical principles that should guide arbitrator’s conduct. Lastly, we will investigate the arbitrator’s failure to disclose, as well as the legal consequences resulting from that. In summary, this investigation aims to demonstrate that, while arbitration is constitutionally recognized as an alternative dispute resolution, there is no legal system capable of meticulously ensuring the control of arbitrator’s conduct, due to the fact that the circumstances that implies disclosure are not properly typified. Moreover, there is no efficacious reaction mechanism to ensure legal security to the contracting parties when the arbitrator has violated his or her duty to disclose and they only became aware of that lately.